L’application du droit de la famille au Maroc : Du « genre » et de la parentalité - Yazid Ben Hounet; Nouri Rupert (L’Année du Maghreb)
This article focuses on the application of family law in Morocco. In order to give a qualitative overview, we conducted an ethnographic survey. The purpose was to understand how family law is implemented in practice in justice court. This research was conducted in the family court of Rabat (family section - court of first instance). In this report, we analyze the administrative and practical functioning of this court that was created after the reform of the family law in 2004. The objective was to study the daily running of the court, the type of cases that were handled, the ways they were handled in relation to the legal texts and the relations to the litigants. This paper deals more specifically with gender issue in the decisions made by the judges, especially on divorces, alimony and parenthood issues and their impact on gender inequalities.